Single-molecule visualization of conformational changes and substrate transport in the vitamin B12 ABC importer BtuCD-F - Joris M. H. Goudsmits (Nature Portfolio, 2017)
The vitamin B12 importer BtuCD-F is a type II ATP-binding cassette transporter. Here the authors use single-molecule fluorescence techniques to analyse ATP hydrolysis and substrate transport in individual BtuCD-F complexes embedded in liposomes, and propose a transport model.